Cracks at Matka arch dam – A Case Study - Tancev L., Shulevski J., Mitovski S. (Austrian Committee on Large Dams, 2018)
The oldest and the only dam built in Republic of Macedonia before World War II, is the Matka reinforced concrete arch dam, which still serves its purpose - forming a reservoir and a head for the production of electric power. It dams the gorge of the River Treska, at a narrow dam site with a V-form, composed of sound and impermeable rock. The dam consists of 10 arches with different radii of curvature, each 3 m high. The thickness of the lowermost arch is 1.6 m, while that of the uppermost is 1.0 m. In July 2012, two cracks in the upper part of the dam were visually recorded, located in the immediate vicinity of the right abutment. Through the cracks a small amount of water licked. The first crack (Crack 1) was on the arch IX, and the second one (Crack 2) on the arch VIII. The visual inspection of the dam, performed at almost full reservoir condition, has shown that Crack 1 was extended along the entire height of the arch IX, while the start point of Crack 2 was 90 cm below the upper edge of the arch VIII, and the end point at the bottom of this arch. The width of Crack 1 was estimated to 1 mm, and of Crack 2 up to 2 mm. Water leakage was visible in the lower part of Crack 1, and throughout the whole length of Crack 2. The presence of limescale and moss suggested that the leakage is continuous and that the cracks are of an older date. In order to find the possible reasons for appearance of the cracks, main attention was paid to the analysis of the measured displacements on the downstream dame face, as well as to the dam and reservoir conditions in the months before the appearance of the cracks. The displacements recorded in the last two series of measurements (2012/2011) were in order of magnitude up to 9 mm, which were also recorded earlier, so that they were rejected as the cause of the cracks. The analyses of the dam and reservoir conditions in the months before the appearance of the cracks showed that since June 16 to June 26, 2012, the reservoir water level was kept low, and it was bellow the cracks. In the same time the air temperature was extremely high for the usual Matka dam site conditions, reaching a maximum value of 33-36 C°. On June 26 and 27, the reservoir was quickly filled with relatively cold water, which caused high temperature stresses in the previously heated upper section of the dam. They widened the cracks, for which there were indications that thay occurred earlier. Despite the two recorded cracks did not jeopardize the stability of the dam, it was decided to be repaired, first of all in order to protect the surrounding concrete from aging and the reinforcement from corroding under the influence of the water that penetrates. Firstly, in May 2013, one-axial gauges for measurement of the crack’s width were installed. Then thermal imaging of the cracks was performed, as well as their injecting with a colored liquid to obtaining important knowledge for the preparation of the remediation solution. Finally, in July 2016, the restoration of the cracks was successfully performed by grouting.